EL IMPACTO DE LOS CONFLICTOS LABORALES EN LAS EMPRESAS AGROEXPORTADORAS DE LIMA, DURANTE EL AÑO 2019 - Morales Muñoz, Roberto (2021)
The research describes work environment that caused labor conflicts in the agro-export companies of Lima in 2019. It also identifies the conflicts started in these companies, describes the way that conflicts are managed and the way to resolve them. The methodology used is qualitative, descriptive, cross-sectional, not experimental. The techniques used were the survey and documentary analysis, the instruments the repetitive questionnaire and digital storage. The population was made up of 811 companies and the sample 261. Four volunteers were surveyed in two stratified samples of 156 bosses and 258 collaborators. The content validity was by expert judgment and the reliability by a pilot of 10 subjects for each sample, through the Crombach Alpha and Likert scale, applying a questionnaire of 20 questions with five alternatives. The study concluded that, in 2019, the impact generated by the conflicts in the agro-export companies of the Lima region was favorable to the company and all the personnel when the conflict was properly managed. The conflicts that arose the most in these companies were identified, as well as those that appeared the least. The way that conflicts were managed in these companies was appropriate for the company and all the staff, despite the weaknesses that must be overcome. Finally, conflicts were resolved through peaceful dispute resolution mechanisms, such as negotiation, mediation, and conciliation with the support of the leadership and following up.